To multiply these two terms and put it into standard form you multiply each individual term in the left parenthesis by each individual term in the right parenthesis.

#y = (color(red)(x) - color(red)(6))(color(blue)(x^2) + color(blue)(6x) + color(blue)(36))# becomes:

#y = (color(red)(x) xx color(blue)(x^2)) + (color(red)(x) xx color(blue)(6x)) + (color(red)(x) xx color(blue)(36)) - (color(red)(6) xx color(blue)(x^2)) - (color(red)(6) xx color(blue)(6x)) - (color(red)(6) xx color(blue)(36))#

#y = x^3 + 6x^2 + 36x - 6x^2 - 36x - 216#

We can now group and combine like terms and put into standard form:

#y = x^3 + 6x^2 - 6x^2 + 36x - 36x - 216#

#y = x^3 + (6x^2 - 6x^2) + (36x - 36x) - 216#

#y = x^3 + 0 + 0 - 216#

#y = x^3 - 216#